Efficacy and tolerability of vortioxetine monotherapy in SSRI-resistant OCD: a retrospective multicenter study - Martiadis, Vassilis; Pessina, Enrico; Cattaneo, Carlo Ignazio; Martini, Azzurra; Raffone, Fabiola; Prodi, Tiziano; Olivola, Miriam; De Berardis, Domenico; Benatti, Beatrice; Dell’Osso, Bernardo Maria (Frontiers in Psychiatry, 2025)
IntroductionTreatment-resistant obsessive-compulsive disorder (OCD) remains a major clinical challenge, with a substantial proportion of patients failing to respond to standard treatment with selective serotonin reuptake inhibitors (SSRI). Vortioxetine, a multimodal antidepressant approved for major depressive disorder, has shown potential advantages in terms of tolerability and cognitive enhancement, but its efficacy in OCD has not been systematically explored.MethodsThis multicenter, retrospective, observational study analyzed the clinical records of 64 adult patients with a DSM-5 diagnosis of OCD who had failed to respond to at least one adequate SSRI trial and were treated with vortioxetine monotherapy (minimum dose: 20 mg/day; duration: ≥8 weeks). The primary outcome was reduction in total Y-BOCS score. Secondary outcomes included changes in HAM-D and HAM-A scores and frequency of adverse events.ResultsAt week 8, 39.1% of patients met responder criteria (≥25% reduction in total Y-BOCS score). The mean Y-BOCS score decreased from 27.1 to 20.7 (p < 0.001). HAM-D and HAM-A scores showed significant improvements (HAM-D: from 21.0 to 12.6; HAM-A: from 26.9 to 16.1; both p < 0.001). The treatment was well tolerated, with nausea (29.7%) and sedation (18.8%) being the most common side effects; no serious adverse events occurred.ConclusionThis study provides preliminary evidence of the efficacy and tolerability of vortioxetine monotherapy in SSRI-resistant OCD. The observed improvements in OCD, depressive and anxiety symptoms suggest that vortioxetine may represent a valuable therapeutic option. Further prospective controlled trials are needed to confirm these findings.